A method for preparing an organic photovoltaically active layer and a photovoltaic device having an active layer

CN122892433APending Publication Date: 2026-10-09HUAZHONG UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611124568.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]本发明所解决的技术问题之一在于提供一种有机光伏活性层制备方法及具有活性层的光伏器件,以解决现有有机光伏器件难以同时实现高光电转换效率和高稳定性的问题

Benefits of technology

[0030]有益效果:本发明提供通过交联锁定的具有浓度梯度的有机光伏活性层制备方法,其通过调节第一混合子层和第二混合子层中的给体/受体比例,使第一混合子层为给体富集层,第二混合子层为受体富集层,从而在活性层厚度方向上形成可设计的浓度梯度结构。具体而言,本发明通过在第一混合子层交联前预先共混给体材料和受体材料,并在第二混合子层沉积前同样预先共混给体材料和受体材料,使两个子层内部均预先形成给受体相界面。随后对给体富集的第一混合子层进行交联处理,以锁定其中已经形成的给受体共混形貌,再沉积受体富集的第二混合子层,从而使活性层中主要给受体相界面的形成不依赖第二混合溶液对第一混合子层的溶胀、溶解或后续互扩散,也即,本发明通过两个预先共混的给体/受体子层,在交联前即于各子层内部构筑给受体相界面,再利用交联网络锁定给体富集下层的共混形貌和垂直浓度梯度,从而在保持充分给受体相界面的同时提高活性层形貌稳定性,实现器件光电转换效率和长期稳定性的协同提升。从而解决了现有技术中,交联清晰双层活性层中给受体相界面主要集中于层间接触区域,活性层中的激子扩散解离受限,难以同时实现高光电转换效率和高稳定性的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122892433A_ABST
    Figure CN122892433A_ABST
Patent Text Reader

Abstract

The application relates to the field of organic photovoltaic technology, and particularly discloses a preparation method of an organic photovoltaic active layer, which comprises the following steps: dissolving a donor material, an acceptor material and a cross-linking agent in a first solvent to form a first mixed solution, wherein the mass of the donor material in the first mixed solution is greater than that of the acceptor material; depositing the first mixed solution on the surface of a substrate or an electron transport layer to form a first mixed sublayer; performing cross-linking treatment on the first mixed sublayer; dissolving the donor material and the acceptor material in a second solvent to form a second mixed solution, wherein the mass of the acceptor material in the second mixed solution is greater than that of the donor material; depositing the second mixed solution on the surface of the first mixed sublayer subjected to the cross-linking treatment to form a second mixed sublayer; and annealing: performing annealing treatment on the obtained double mixed layer thin film to obtain a cross-linking stable organic photovoltaic active layer. The application can make the organic photovoltaic device simultaneously obtain higher photoelectric conversion efficiency and higher long-term stability, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of organic photovoltaic technology, specifically to a method for preparing an organic photovoltaic active layer and a photovoltaic device having an active layer. Background Technology

[0002] Compared to traditional silicon-based solar cells, organic solar cells offer advantages such as lightweight, flexibility, solution-processability, and suitability for roll-to-roll large-area production, demonstrating irreplaceable differentiated application value in the photovoltaic market. Organic solar cell devices are composed of multiple stacked functional layers, typically including a conductive substrate and electrodes, a charge transport layer, and an active layer. In the conductive substrate and electrodes, a glass or flexible polymer substrate coated with a transparent conductive oxide such as indium tin oxide serves as the anode, through which sunlight enters. A metal electrode acts as the counter electrode to collect charge. The charge transport layer, located between the active layer and the electrodes, includes a hole transport layer and an electron transport layer, responsible for selectively extracting and transporting corresponding charge carriers while blocking opposite charges to reduce recombination losses. The active layer is typically composed of a blend of electron donors and electron acceptors. After light irradiation, the active layer sequentially completes five key steps: photon absorption, exciton generation, exciton diffusion, exciton dissociation, and charge carrier transport. The active layer is the core site of photoelectric conversion and a decisive factor in determining the efficiency and stability of the device. This is because all five photoelectric conversion steps mentioned above are completed within the active layer, and its quality directly determines whether the device can efficiently convert photons into charges. In addition, the morphology of the active layer is closely related to its performance. An ideal active layer morphology should have sufficient donor-acceptor interfaces to ensure exciton dissociation and bicontinuous charge transport channels to ensure carrier collection. This requirement is closely related to the morphology of the active layer. Furthermore, the active layer is usually in a thermodynamically metastable state and is prone to molecular diffusion, excessive aggregation of acceptors, and phase separation coarsening under photothermal stress, which are the main sources of device performance degradation.

[0003] Currently, the biggest challenge for organic solar cells is their low conversion efficiency. Achieving both high photoelectric conversion efficiency and high stability in organic photovoltaic devices is a major research challenge. Thanks to the rapid development of Y-series small-molecule non-fullerene acceptors, organic solar cells based on bulk heterojunction (BHJ) structures have achieved efficiencies exceeding 20%. However, BHJs are typically in a thermodynamically metastable state, and under long-term thermal stress or illumination, they are prone to molecular diffusion, excessive acceptor aggregation, and phase separation coarsening, leading to rapid initial efficiency degradation and insufficient long-term stability. To overcome the limitations of BHJs in morphology control, researchers have developed sequential deposition techniques. For example, Chinese patent CN202311382610.8 proposes a layer-by-layer organic solar cell device based on a cross-linked structure. By depositing donor and acceptor layers separately using a layer-by-layer (LBL) process, the donor and acceptor are enriched near the anode and cathode, respectively, which is beneficial for charge collection. However, the problem with this approach is that while the pseudo-bilayer structure (PBL) of sequential deposition (LBL) can regulate the vertical distribution of donors and acceptors, the solvent in the upper layer may cause the lower layer to swell, dissolve, or become over-mixed, making it difficult to precisely control the vertical component distribution. If an overly clear donor / acceptor bilayer structure is formed, insufficient donor-acceptor interface will affect exciton dissociation and device efficiency.

[0004] Crosslinking strategies have been proven to effectively suppress molecular diffusion, anchor the morphology of the active layer, and improve stability. For example, Chinese patent CN202311738026.1 proposes an organic solar cell based on in-situ crosslinking and curing of the photovoltaic active layer. The photovoltaic active layer is a bulk heterojunction (BHJ) structure, a pseudo-planar heterojunction (PPHJ) structure, or a planar heterojunction (PHJ) bilayer structure. The photovoltaic active layer contains a polymer donor and two small molecule acceptor materials. In-situ crosslinking occurs between the functional groups at the ends of the side chains of the small molecule acceptor materials, generating oligomeric acceptors with smaller diffusion coefficients, thereby suppressing the diffusion behavior of the small molecule acceptors. Furthermore, Chinese patent CN202511609735.9 discloses an organic photovoltaic cell and its preparation method for achieving crosslinking and curing of the active layer. This method broadens the range of crosslinking conditions by introducing allyl / acrylate co-crosslinking agents to achieve low-temperature crosslinking and curing of the active layer. However, none of the above crosslinking schemes can solve the problem of how to simultaneously achieve high photoelectric conversion efficiency and high stability in organic photovoltaic devices.

[0005] Therefore, the present invention aims to develop an organic photovoltaic active layer preparation method and a photovoltaic device with an active layer that has sufficient donor-acceptor interface, controllable vertical concentration gradient and morphology locking capability, so as to better meet practical needs. Summary of the Invention

[0006] One of the technical problems solved by this invention is to provide a method for preparing an organic photovoltaic active layer and a photovoltaic device with an active layer, so as to solve the problem that existing organic photovoltaic devices are difficult to achieve both high photoelectric conversion efficiency and high stability at the same time.

[0007] The technical problem solved by this invention is achieved by the following technical solution: A method for preparing an organic photovoltaic active layer includes the following steps: Preparation of the first mixed sublayer: The donor material, acceptor material, and crosslinkable agent are dissolved in a first solvent to form a first mixed solution, wherein the mass of the donor material in the first mixed solution is greater than the mass of the acceptor material; the first mixed solution is deposited on the surface of a substrate or an electron transport layer to form a donor-enriched first mixed sublayer; the first mixed sublayer is crosslinked to lock the donor-acceptor blend morphology already formed in the first mixed sublayer; in this step, the first mixed sublayer acquires solvent erosion resistance, thereby maintaining its basic morphology and component distribution during the subsequent deposition of the second mixed sublayer; Preparation of the second mixed sublayer: Donor and acceptor materials are dissolved in a second solvent to form a second mixed solution, wherein the mass of acceptor material in the second mixed solution is greater than that of donor material; the second mixed solution is deposited on the surface of the cross-linked first mixed sublayer to form a acceptor-enriched second mixed sublayer. Since the first mixed sublayer has already formed a cross-linked network, the second mixed solution is less likely to significantly wash away or dissolve the underlying layer during deposition, which is beneficial for obtaining a controllable and repeatable vertical concentration gradient structure. Annealing: The obtained double-mixed-layer film is annealed to obtain a cross-linked and stable organic photovoltaic active layer. The first and second mixed sublayers in the active layer together form a donor / acceptor concentration gradient that varies along the thickness direction of the active layer.

[0008] Furthermore, in the first mixed sublayer preparation step, the concentration of the first mixed solution is 6-15 mg / mL, and the mass ratio of donor material to acceptor material is 2-10:1; the concentration of the second mixed solution is 8-20 mg / mL, and the mass ratio of donor material to acceptor material is 1:2-10. In this invention, by adjusting the donor / acceptor ratio in the first and second mixed sublayers, the intensity of the vertical concentration gradient in the active layer can be controlled, thereby achieving a better balance between photoelectric conversion efficiency and stability.

[0009] Preferably, the concentration of the first mixed solution is 6~10 mg / mL, and the concentration of the second mixed solution is 8~12 mg / mL.

[0010] More preferably, the concentration of the first mixed solution is 9 mg / mL, and the concentration of the second mixed solution is 10 mg / mL.

[0011] Preferably, the mass ratio of donor material to acceptor material in the first mixed solution is 4~6:1; and the mass ratio of donor material to acceptor material in the second mixed solution is 1:4~6.

[0012] More preferably, the mass ratio of donor material to acceptor material in the first mixed solution is 4:1; and the mass ratio of donor material to acceptor material in the second mixed solution is 1:4.

[0013] Furthermore, in the first and second mixed solutions, the donor material is a conjugated polymer, including one or more of PM6, PBDB-T, D18, PTB7-Th and their derivatives; the acceptor material is a non-fullerene acceptor material, including one or more of BTP-eC9, Y6, L8-BO, N3, BTP-4Cl and their derivatives.

[0014] In a preferred embodiment, in the first mixed solution and the second mixed solution, the donor material is PM6 and the acceptor material is BTP-eC9.

[0015] Furthermore, in the first mixed solution, the amount of crosslinkable agent added accounts for 0.5 to 10% of the mass of the donor material.

[0016] In a preferred embodiment, the amount of crosslinkable agent added to the first mixed solution is 2-4% of the mass of the donor material. More preferably, it is 3%.

[0017] Furthermore, the crosslinkable agent is a crosslinkable agent that can form a crosslinked structure with the donor material under light or heat treatment conditions; the crosslinkable agent includes one or more of the following: azide crosslinkable agents, peroxide crosslinkable agents, alkenyl crosslinkable agents, alkynyl crosslinkable agents, and epoxy crosslinkable agents; the azide crosslinkable agent includes one or more of the following: bisazide crosslinkable agents, arylazide crosslinkable agents, and bisbenzylazide crosslinkable agents.

[0018] In a preferred embodiment, the crosslinking agent is 2,6-bis(4-azidobenzyl)cyclohexanone, abbreviated as BAC. BAC reacts under ultraviolet light to generate a highly reactive intermediate, which then crosslinks with the side chains of the donor polymer, thereby forming a stable crosslinked network in the first mixed sublayer.

[0019] Furthermore, in the preparation of the first mixed sublayer, the crosslinking treatment is ultraviolet (UV) irradiation treatment with a UV wavelength of 254 nm and an irradiation time of 30–120 s. In a preferred embodiment, the irradiation time is 90 s. UV irradiation causes the crosslinkable agent in the first mixed sublayer to undergo a crosslinking reaction, forming a crosslinked, stable donor-enriched lower layer.

[0020] Furthermore, in the annealing step, the annealing temperature is 80~120 ℃, and the annealing time is 3~10 min.

[0021] In the preferred embodiment, the annealing temperature is 90~100 ℃ and the annealing time is 4~8 min. In a further preferred embodiment, the annealing temperature is 100 ℃ and the annealing time is 5 min.

[0022] Furthermore, the total thickness of the organic photovoltaic active layer is 80~150 nm, the thickness of the first hybrid sublayer is smaller than that of the second hybrid sublayer, and the ratio of the thickness of the first hybrid sublayer to the thickness of the second hybrid sublayer is 4~5:6~8.

[0023] In the preferred embodiment, the total thickness of the organic photovoltaic active layer is 110 nm, wherein the thickness of the first hybrid sublayer is 50 nm and the thickness of the second hybrid sublayer is 60 nm.

[0024] Furthermore, the first solvent and the second solvent include one or more of chlorobenzene, chloroform, toluene, xylene, trimethylbenzene, o-dichlorobenzene, chloronaphthalene, and tetrahydrofuran.

[0025] In a preferred embodiment, the first solvent is chlorobenzene and the second solvent is chloroform.

[0026] Furthermore, during the preparation of the first and second mixed sublayers, the deposition method can be spin coating, blade coating, slot coating, spraying, or printing. Preferably, spin coating is used, with a rotation speed of 3000~4000 rpm.

[0027] Furthermore, during the preparation of the second mixed sublayer, DIO is added to the second mixed solution. The DIO is 1,8-diiodooctane, and the proportion of DIO in the second mixed solution is 0.2~3.0 vol%, preferably 0.5 vol.

[0028] A photovoltaic device having an active layer, wherein the active layer is prepared by any of the methods described above.

[0029] In a preferred embodiment, the photovoltaic device adopts a reverse structure or a forward structure, and the photovoltaic device sequentially includes an ITO substrate layer, a ZnO electron transport layer, the active layer described in this invention, and a MoO3 hole transport layer, and also includes an Ag electrode.

[0030] Beneficial Effects: This invention provides a method for preparing an organic photovoltaic active layer with a concentration gradient through cross-linking locking. By adjusting the donor / acceptor ratio in the first and second mixed sublayers, the first mixed sublayer becomes a donor-rich layer, and the second mixed sublayer becomes an acceptor-rich layer, thereby forming a designable concentration gradient structure along the thickness direction of the active layer. Specifically, this invention pre-blends the donor and acceptor materials before cross-linking the first mixed sublayer, and similarly pre-blends the donor and acceptor materials before depositing the second mixed sublayer, thus pre-forming a donor-acceptor phase interface within both sublayers. Subsequently, the first mixed sublayer enriched with donors is cross-linked to lock the already formed donor-acceptor blend morphology. Then, a second mixed sublayer enriched with acceptors is deposited. This ensures that the formation of the main donor-acceptor interface in the active layer is independent of the swelling, dissolution, or subsequent interdiffusion of the first mixed sublayer by the second mixed solution. In other words, this invention constructs a donor-acceptor interface within each sublayer before cross-linking using two pre-blended donor / acceptor sublayers. The cross-linking network then locks the blend morphology and vertical concentration gradient of the donor-enriched lower layer. This improves the stability of the active layer morphology while maintaining a sufficient donor-acceptor interface, achieving a synergistic improvement in both photoelectric conversion efficiency and long-term stability. This solves the problem in existing technologies where the donor-acceptor interface in a clearly cross-linked bilayer active layer is mainly concentrated in the interlayer contact region, limiting exciton diffusion and dissociation in the active layer, making it difficult to simultaneously achieve high photoelectric conversion efficiency and high stability.

[0031] Compared to the traditional cross-linked bilayer structure where a relatively pure donor layer is cross-linked first, followed by the deposition of a relatively pure acceptor layer, the active layer of this invention contains acceptor material in the first mixed sublayer before cross-linking, and donor material in the second mixed sublayer before deposition. Therefore, donor-acceptor interfaces are pre-formed within both sublayers. The formation of these interfaces in this invention does not depend on the swelling, dissolution, or subsequent interdiffusion of the first mixed sublayer by the second mixed solution. Even after the first mixed sublayer undergoes sufficient cross-linking and exhibits strong resistance to solvent erosion, the donor-acceptor interfaces formed before cross-linking are still retained within it. Simultaneously, the acceptor-enriched second mixed sublayer itself also possesses donor-acceptor interfaces, thereby distributing the effective exciton dissociation interface across multiple thickness regions of the active layer, rather than concentrating it only at the contact point between the two sublayers. In this invention, the dual-mixed-layer structure reduces the diffusion distance required for excitons to reach the donor-acceptor interface, increases the exciton dissociation probability, and reduces exciton recombination loss. The opposite donor / acceptor ratios between the two sublayers create a vertical concentration gradient, which is beneficial for the transport and collection of electrons and holes along the corresponding directions. The cross-linked network in the first mixed sublayer can suppress component migration, excessive acceptor aggregation, and phase separation coarsening during subsequent solution deposition and long-term thermal aging. Therefore, this invention does not improve stability by reducing the donor-acceptor mixed phase, sacrificing the donor-acceptor interface, or lowering photoelectric conversion efficiency. Instead, it locks in the active layer morphology while preserving a sufficient donor-acceptor interface, thereby simultaneously improving the photoelectric conversion efficiency and long-term stability of the device.

[0032] This invention involves first depositing a donor-enriched mixed lower layer containing a crosslinking agent and then photocrosslinking it, followed by depositing an acceptor-enriched mixed upper layer to form a crosslinked and stable bi-mixed layer concentration gradient structure. This method is simple, compatible with solution-based and sequential deposition processes, and can be extended to different donor / acceptor material systems for the fabrication of high-efficiency, high-stability organic photovoltaic devices. Attached Figure Description

[0033] Figure 1 This is a flowchart illustrating the preparation process of the organic photovoltaic active layer in Example 1.

[0034] Figure 2 The current density-voltage curves of the photovoltaic devices prepared in Example 1 and Comparative Examples 1-3 are shown.

[0035] Figure 3 The graph shows the storage stability of the photovoltaic devices prepared in Example 1 and Comparative Examples 1-3.

[0036] Figure 4 The graph shows the thermal stability of the photovoltaic devices prepared in Example 1 and Comparative Examples 1-3.

[0037] Figure 5The above is a statistical graph showing the light stability of the photovoltaic devices prepared in Example 1 and Comparative Examples 1-3.

[0038] Figure 6 The current density-voltage curves of the CGBL photovoltaic devices prepared in Examples 1, 2 and 3 are statistical graphs.

[0039] Figure 7 The current density-voltage curves of the CGBL photovoltaic devices prepared in Examples 1, 4, and 5 are statistical graphs.

[0040] Figure 8 The current density-voltage curves of the CGBL photovoltaic devices prepared in Examples 1, 6, 7 and 8 are statistical graphs.

[0041] Figure 9 The thermal stability statistics of the CGBL photovoltaic devices prepared in Examples 9-11 and the BHJ devices prepared in Comparative Examples 4-6 are shown in the figure.

[0042] Figure 10 AFM images of the photovoltaic devices prepared in Example 1 and Comparative Examples 1-3 are shown.

[0043] Figure 11 The figures show the test results of the double cantilever beam photovoltaic devices prepared in Example 1 and Comparative Examples 1-3. Detailed Implementation

[0044] To make the technical means, creative features, objectives and effects of this invention easier to understand, the invention will be further described below with reference to specific embodiments.

[0045] Example 1

[0046] like Figure 1 As shown, the method for preparing the organic photovoltaic active layer of the present invention includes the following steps: Preparation of the first mixed sublayer: The donor material, the acceptor material and the crosslinking agent are dissolved in a first solvent to form a first mixed solution, wherein the donor material is PM6, the acceptor material is BTP-eC9, the mass ratio of the donor material to the acceptor material is 4:1, the first solvent is chlorobenzene, the crosslinking agent is BAC, the mass ratio of BAC to PM6 is 3%, and the total concentration of the first solution is 9 mg / mL. The first mixed solution was spin-coated onto a ZnO layer, followed by UV irradiation for 90 s to crosslink BAC with the PM6 side chains, forming a donor-enriched crosslinked lower layer.

[0047] Preparation of the second mixed sublayer: The donor material PM6 and the acceptor material BTP-eC9 are dissolved in a second solvent to form a second mixed solution, wherein the mass ratio of PM6 to BTP-eC9 is 1:4, the total concentration of the second mixed solution is 12 mg / mL, and 0.5 vol% DIO is added to the second mixed solution as a processing additive; the second mixed solution is spin-coated onto the cross-linked first mixed sublayer, that is, the donor-enriched cross-linked lower layer.

[0048] Annealing: The obtained double-mixed layer film was annealed at 100 °C for 5 min to obtain a CGBL active layer with a total thickness of about 110 nm, wherein the thickness of the first mixed sublayer is about 50 nm and the thickness of the second mixed sublayer is about 60 nm.

[0049] The prepared CGBL active layer is applied to a photovoltaic device, and the photovoltaic device structure is ITO / ZnO / active layer / MoO3 / Ag.

[0050] Example 2

[0051] The difference between this embodiment and Embodiment 1 is that, in the first mixed sublayer preparation step, the mass ratio of donor material to acceptor material in the first mixed solution is 2:1; and the mass ratio of donor material to acceptor material in the second mixed solution is 1:2, with the rest being the same.

[0052] Example 3

[0053] The difference between this embodiment and Embodiment 1 is that, in the first mixed sublayer preparation step, the mass ratio of donor material to acceptor material in the first mixed solution is 8:1; and the mass ratio of donor material to acceptor material in the second mixed solution is 1:8, with the rest being the same.

[0054] Example 4

[0055] The difference between this embodiment and Embodiment 1 is that the amount of crosslinkable agent added in the first mixed solution accounts for 2% of the mass of the donor material, and the rest are the same.

[0056] Example 5

[0057] The difference between this embodiment and Embodiment 1 is that the amount of crosslinkable agent added in the first mixed solution accounts for 4% of the mass of the donor material, and the rest is the same.

[0058] Example 6

[0059] The difference between this embodiment and Embodiment 1 is that the UV irradiation time in the preparation of the first mixed sublayer is 30s, while the rest are the same.

[0060] Example 7

[0061] The difference between this embodiment and Embodiment 1 is that the UV irradiation time in the preparation of the first mixed sublayer is 60s, while the rest are the same.

[0062] Example 8

[0063] The difference between this embodiment and Embodiment 1 is that the UV irradiation time in the preparation of the first mixed sublayer is 120s, while the rest are the same.

[0064] Example 9

[0065] The difference between this embodiment and Embodiment 1 is that in the first and second mixed solutions, the donor material is PM6 and the acceptor material is Y6, while the rest are the same.

[0066] Example 10

[0067] The difference between this embodiment and Embodiment 1 is that in the first and second mixed solutions, the donor material is PBDB-T and the acceptor material is Y6, while the rest are the same.

[0068] Example 11

[0069] The difference between this embodiment and Embodiment 1 is that in the first and second mixed solutions, the donor material is D18 and the acceptor material is N3, while the rest are the same.

[0070] Compare with Example 1 In this comparative example, PM6 and BTP-eC9 were mixed in chloroform at a ratio of 1:1.2 to obtain a total concentration of 17.6 mg / mL, and 0.5 vol% DIO was added. After spin coating, the mixture was heat-annealed at 100 °C for 5 min to obtain the BHJ active layer. The photovoltaic device fabricated using this active layer is a BHJ device with a structure of ITO / ZnO / active layer / MoO3 / Ag.

[0071] Compare with Example 2 In this comparative example, the active layer was prepared by first spin-coating PM6 chlorobenzene solution, then spin-coating BTP-eC9 chloroform solution, and finally thermally annealing at 100 °C for 5 min to obtain the PBL active layer. The photovoltaic device fabricated using this active layer is a PBL device, and the photovoltaic device structure is ITO / ZnO / active layer / MoO3 / Ag.

[0072] Compare with Example 3 In this comparative example, during the preparation of the active layer, a PM6 lower layer containing 3 wt% BAC was first prepared and UV crosslinked, followed by the deposition of a BTP-eC9 upper layer, forming a relatively clear donor / acceptor bilayer structure. The photovoltaic device fabricated using this active layer is a CBL device, with a structure of ITO / ZnO / active layer / MoO3 / Ag.

[0073] Compare with Example 4 The difference between this comparative example and Comparative Example 1 is that the donor material is PM6 and the acceptor material is Y6, otherwise they are the same.

[0074] Compare with Example 5 The difference between this comparative example and Comparative Example 1 is that the donor material is PBDB-T and the acceptor material is Y6, otherwise they are the same.

[0075] Compare with Example 6 The difference between this comparative example and Comparative Example 1 is that the donor material is D18 and the acceptor material is N3, otherwise they are the same.

[0076] Compare with Example 7 The difference between this comparative example and Example 1 is that in the first mixed sublayer preparation step, the mass ratio of donor material to acceptor material is 12:1; and in the second mixed solution, the mass ratio of donor material to acceptor material is 1:12. The photovoltaic device prepared under these conditions has extremely low photoelectric conversion efficiency and no practical application value.

[0077] Compare with Example 8 The difference between this comparative example and Example 1 is that in the first mixed sublayer preparation step, the mass ratio of donor material to acceptor material is 1:1; and in the second mixed solution, the mass ratio of donor material to acceptor material is also 1:1. The photovoltaic device prepared under these conditions also has extremely low photoelectric conversion efficiency and no practical application value.

[0078] Compare with Example 9 The difference between this comparative example and Example 1 is that in the first mixed sublayer preparation step, the mass ratio of donor material to acceptor material is 1:4; and in the second mixed solution, the mass ratio of donor material to acceptor material is 4:1, with the rest remaining the same. As a result, because the donor material is a polymer and the acceptor material is a small molecule, solvents that can dissolve polymers readily dissolve small molecules, making it impossible to prepare an ideal double-mixed layer film, and subsequent photovoltaic device fabrication was not carried out.

[0079] Test methods: To verify the performance of the obtained active layer and photovoltaic device, referring to GB / T 6495-2025, the following test methods were used in the above embodiments and comparative examples: the photoelectric conversion efficiency (PCE), open circuit voltage (Voc), short circuit current density (Jsc), and fill factor (FF) of the device were tested by current density-voltage curves; the thermal stability, light stability, and storage stability of the device were evaluated by 85 ℃ thermal aging, continuous light aging, and dark storage tests; the changes in the surface morphology of the film before and after thermal aging were observed by atomic force microscopy; and the cohesive energy of the active layer was tested by double cantilever beams.

[0080] Table 1 shows the statistical results of the photovoltaic devices prepared in Examples 1-8 and Comparative Examples 1-3. Table 2 shows the statistical results of the stability T80 time of the photovoltaic devices prepared in Examples 1 and Comparative Examples 1-3.

[0081] Table 1. Statistical Table of Photovoltaic Device Performance

[0082] Table 2. Stability Statistics of Photovoltaic Devices (T80 Time)

[0083] Example 1: The current density-voltage curves of the photovoltaic devices prepared in Comparative Examples 1-3 are shown below. Figure 2 As shown, combined with Figure 2 As shown in Table 1, the photovoltaic device prepared by this invention has a significantly higher photoelectric conversion efficiency than traditional BHJ devices, PBL devices, and CBL devices, and it is also universally applicable.

[0084] The storage stability statistics of CGBL photovoltaic devices prepared in Example 1 and Comparative Examples 1-3 are as follows: Figure 3 As shown, combined with Figure 3 As shown in Table 2, the photovoltaic device products prepared by this invention have significantly better storage stability than traditional active layer BHJ devices and PBL devices.

[0085] The thermal stability statistics of the CGBL photovoltaic devices prepared in Example 1 and Comparative Examples 1-3 are as follows: Figure 4 As shown, combined with Figure 4 As shown in Table 2, the product prepared by this invention has significantly better thermal stability than the traditional active layer BHJ device and PBL device.

[0086] The statistical analysis of the light stability of CGBL photovoltaic devices prepared in Example 1 and Comparative Examples 1-3 is as follows: Figure 5 As shown, combined with Figure 5 As shown in Table 2, the results indicate that the product prepared by this invention has significantly better light stability than traditional active layer BHJ devices and PBL devices.

[0087] The current density-voltage curves of the CGBL photovoltaic devices prepared in Examples 1, 2, and 3 are statistically analyzed as follows: Figure 6 As shown, when the mass ratio of donor material to acceptor material is within the preferred range, the photovoltaic device prepared by this invention has better photoelectric conversion efficiency.

[0088] The current density-voltage curves of the CGBL photovoltaic devices prepared in Examples 1, 4, and 5 are statistically analyzed as follows: Figure 7 As shown, when the amount of crosslinking agent added is within the preferred range, the photovoltaic device prepared by the present invention has better photoelectric conversion efficiency.

[0089] The current density-voltage curves of the CGBL photovoltaic devices prepared in Examples 1, 6, 7, and 8 are statistically analyzed as follows: Figure 8 As shown, with proper control of UV irradiation conditions, the photovoltaic device prepared by this invention has better photoelectric conversion efficiency.

[0090] The thermal stability statistics of the CGBL photovoltaic devices prepared in Examples 9-11 and the BHJ devices prepared in Comparative Examples 4-6 are as follows: Figure 9 As shown, when using different photoactive layer materials, the photostability of the CGBL structure active layer device prepared by this invention is superior to that of the traditional BHJ structure device. This demonstrates that the method described in this invention has universality.

[0091] Compared to traditional BHJ, PBL, and clear bilayer (CBL) active layers, the CGBL active layer of this invention optimizes the vertical distribution of donors and acceptors while maintaining a sufficient donor-acceptor interface, thus balancing exciton dissociation, carrier transport, and charge collection. Since both the upper and lower layers are donor / acceptor hybrid layers, CGBL avoids the problem of insufficient donor-acceptor interface in CBL structures; simultaneously, the lower cross-linked network improves structural stability, preventing morphological runaway during subsequent fabrication and aging of ordinary BHJ or PBL active layers. Therefore, this invention can further improve photovoltaic performance without sacrificing device efficiency. The device in Example 1 achieved a photoelectric conversion efficiency of 18.53%, which is higher than the 17.54% of the BHJ device in Comparative Example 1 and the 18.01% of the PBL device in Comparative Example 2, and significantly higher than the 13.48% of the CBL device in Comparative Example 3.

[0092] This invention can significantly reduce the rapid performance degradation phase in the early stages of thermal aging. Because the cross-linked network restricts the thermal motion of donor and acceptor molecules and slows down the diffusion and excessive aggregation of small molecule acceptors under thermal stress, the CGBL active layer can better maintain its original morphology and charge transport path in the early stages of high-temperature aging, thereby reducing the rapid initial performance decline common in organic photovoltaic devices. After 100 h of thermal aging in a nitrogen environment at 85 ℃, the PCE of the BHJ device in Comparative Example 1 and the PBL device in Comparative Example 2 rapidly decreased to 92.7% and 94.3% of their initial values, respectively, while the CGBL device in Example 1 still maintained an initial efficiency of over 97.1%; the thermal aging T80 lifetimes were 907 h for BHJ, 3728 h for PBL, 7013 h for CBL, and 6370 h for CGBL.

[0093] This invention improves long-term storage stability and light-induced stability. The cross-linked, stable bi-mixed-layer concentration gradient structure not only suppresses thermally induced morphological changes but also maintains a relatively stable vertical component distribution and phase separation structure under long-term storage and continuous light-induced conditions, thereby reducing efficiency degradation caused by morphological rearrangement, acceptor aggregation, and charge transport path disruption. The CGBL device exhibits a T80 lifetime of approximately 59,000 h in dark-state storage tests and approximately 2,074 h in continuous AM 1.5G spectral irradiation stability tests.

[0094] This invention can suppress heat-induced morphological degradation. For example... Figure 10 As shown, the top four images are before accelerated thermal aging at 100℃ for 100h, and the bottom four images are after accelerated thermal aging. Rq in the figures represents roughness. It can be clearly seen that the CGBL structure device in this invention has a more stable morphology and a smaller increase in roughness after thermal aging compared to the traditional BHJ and PBL structure devices.

[0095] Specifically, the BHJ film in Comparative Example 1 and the PBL film in Comparative Example 2 are prone to phase region coarsening, increased surface roughness, and excessive acceptor aggregation during thermal aging, thereby reducing the effective acceptor interface and increasing recombination loss. In contrast, the cross-linked network in the CGBL structure of Example 1 of this invention can lock the morphology of the active layer, restricting molecular migration and large-scale phase separation during thermal aging. After accelerated thermal aging at 100 °C for 100 h, the RMS roughness of the BHJ film increased from 0.90 nm to 2.08 nm, and that of the PBL film increased from 1.15 nm to 1.77 nm; while that of the CGBL film only increased from 1.32 nm to 1.57 nm.

[0096] This invention also improves the mechanical robustness of the active layer. The formation of the cross-linked network in this invention not only stabilizes the nanophase separation morphology of the active layer but also enhances the internal interconnections and crack propagation resistance of the film, resulting in better structural integrity of the active layer during subsequent processing, thermal cycling, or device operation. Figure 11 As shown, the double cantilever beam test reveals that the cohesive energy of the CGBL film is 3.19 J / m. 2 It is higher than BHJ's 0.99 J / m 2 And PBL's 1.20 J / m 2 .

[0097] This invention has good versatility. The method does not rely on a single donor / acceptor material combination, but rather achieves morphology stabilization through a general structural design of donor-enriched mixed lower layer crosslinking combined with acceptor-enriched mixed upper layer deposition. Therefore, it can be extended to various organic photovoltaic material systems. Besides the PM6:BTP-eC9 system, this CGBL treatment strategy can also be extended to PM6:Y6, PBDB-T:Y6, and D18:N3 systems. After thermal aging at 85 ℃ for 1000 h, the CGBL devices maintained initial efficiencies of 95% for the PM6:Y6 system, 92% for the PBDB-T:Y6 system, and 91% for the D18:N3 system, while the corresponding BHJ devices all dropped below 80%.

[0098] In this invention, BHJ stands for Bulk Heterojunction, referring to a structure in which donors and acceptors co-exist in a single active layer to form an interpenetrating network. LBL / PBL stands for Layer-by-layer / Pseudo-bilayer, referring to a sequentially deposited / pseudo-bilayer structure. CGBL stands for Concentration-gradient bilayer, specifically referring to a concentration-gradient active layer in this invention where both upper and lower layers are D / A mixed layers with opposite ratios, and are stabilized by a crosslinking network. CBL stands for Clear-phase bilayer, typically referring to a stack of a purer donor layer and a purer acceptor layer. BAC stands for 2,6-Bis(4-azidobenzyl)cyclohexanone, the preferred azido photocrosslinking agent used in this invention. T80 is the time required for the device efficiency to drop to 80% of its initial efficiency.

[0099] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an organic photovoltaic active layer, characterized in that, Includes the following steps: Preparation of the first mixed sublayer: The donor material, the acceptor material, and the crosslinkable agent are dissolved in a first solvent to form a first mixed solution, wherein the mass of the donor material in the first mixed solution is greater than the mass of the acceptor material; The first mixed solution is deposited on the substrate or electron transport layer surface to form a donor-enriched first mixed sublayer. The first hybrid sublayer is cross-linked; Preparation of the second mixed sublayer: The donor material and the acceptor material are dissolved in a second solvent to form a second mixed solution, wherein the mass of the acceptor material in the second mixed solution is greater than the mass of the donor material; The second mixed solution is deposited on the surface of the cross-linked first mixed sublayer to form a receptor-enriched second mixed sublayer. Annealing: The obtained double-mixed-layer film is annealed to obtain a cross-linked and stable organic photovoltaic active layer.

2. The method for preparing the organic photovoltaic active layer according to claim 1, characterized in that, In the first mixed sublayer preparation step, the concentration of the first mixed solution is 6~15 mg / mL, and the mass ratio of donor material to acceptor material is 2~10:1; the concentration of the second mixed solution is 8~20 mg / mL, and the mass ratio of donor material to acceptor material is 1:2~10.

3. The method for preparing the organic photovoltaic active layer according to claim 2, characterized in that, In the first and second mixed solutions, the donor material is a conjugated polymer, including one or more of PM6, PBDB-T, D18, PTB7-Th and their derivatives; the acceptor material is a non-fullerene acceptor material, including one or more of BTP-eC9, Y6, L8-BO, N3, BTP-4Cl and their derivatives.

4. The method for preparing the organic photovoltaic active layer according to claim 1, characterized in that, In the first mixed solution, the amount of crosslinkable agent added accounts for 0.5 to 10% of the mass of the donor material.

5. The method for preparing the organic photovoltaic active layer according to claim 4, characterized in that, The crosslinkable agent is a crosslinkable agent that can form a crosslinked structure with the donor material under light or heat treatment conditions; the crosslinkable agent includes one or more of the following: azide crosslinkable agents, peroxide crosslinkable agents, alkenyl crosslinkable agents, alkynyl crosslinkable agents, and epoxy crosslinkable agents; the azide crosslinkable agent includes one or more of the following: bisazide crosslinkable agents, arylazide crosslinkable agents, and bisbenzylazide crosslinkable agents.

6. The method for preparing an organic photovoltaic active layer according to claim 1, characterized in that, In the preparation of the first mixed sublayer, the crosslinking treatment is a UV irradiation treatment with a UV wavelength of 254 nm and an irradiation time of 30~120 s.

7. The method for preparing the organic photovoltaic active layer according to claim 1, characterized in that, In the annealing step, the annealing temperature is 80~120 ℃ and the annealing time is 3~10 min.

8. The method for preparing an organic photovoltaic active layer according to claim 1, characterized in that, The total thickness of the organic photovoltaic active layer is 80~150 nm. The thickness of the first mixed sublayer is smaller than that of the second mixed sublayer, and the ratio of the thickness of the first mixed sublayer to the thickness of the second mixed sublayer is 4~5:6~8.

9. The method for preparing an organic photovoltaic active layer according to claim 1, characterized in that, The first solvent and the second solvent include one or more of chlorobenzene, chloroform, toluene, xylene, trimethylbenzene, o-dichlorobenzene, chloronaphthalene, and tetrahydrofuran.

10. A photovoltaic device having an active layer, characterized in that, The active layer is prepared by the method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Layer-by-layer processing organic solar cell device based on cross-linked structure and preparation method thereof

    CN117279405A

  • Organic solar cell based on photovoltaic active layer in-situ cross-linking curing and preparation method thereof

    CN117794262A

  • Organic photovoltaic cell capable of realizing crosslinking and curing of active layer and preparation method of organic photovoltaic cell

    CN121692911A